2016
DOI: 10.1111/add.13348
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients infected with HIV through use of injected drugs compared to patients infected through sexual transmission: late presentation, delayed anti‐retroviral treatment and higher mortality

Abstract: In Spain, patients who acquire HIV infection through use of injected drugs appear to have a higher risk of late presentation, delayed initiation of anti-retroviral treatment and progression to AIDS and death than patients who acquire HIV by sexual transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 45 publications
2
18
0
Order By: Relevance
“…Recent data from The Joint United Nations Programme on HIV/AIDS described a 19% decline in AIDS-related deaths from 2011 to 2014, and a 35% decline from 2005 to 2014 [1**]. Among HIV-positive PWID however, the leading cause of death remains HIV/AIDS-related causes [2,3**,7,29,30,31*,3234,35*,36**,37], reflecting suboptimal levels of ART access, and adherence in this population.…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data from The Joint United Nations Programme on HIV/AIDS described a 19% decline in AIDS-related deaths from 2011 to 2014, and a 35% decline from 2005 to 2014 [1**]. Among HIV-positive PWID however, the leading cause of death remains HIV/AIDS-related causes [2,3**,7,29,30,31*,3234,35*,36**,37], reflecting suboptimal levels of ART access, and adherence in this population.…”
Section: Hiv/aids-related Mortality In the Modern Treatment Eramentioning
confidence: 99%
“…Research has underscored the impact of liver-related diseases [2,11,30,31*,50], including hepatitis C virus (HCV) [7,34,51], on premature mortality among HIV-positive PWID, with HIV – HCV co-infected individuals having a significantly increased risk of death [11]. A 15-year prospective cohort study investigating predictors of liver-related death in a cohort of PWID in Vancouver showed that HIV seropositivity was independently and positively associated with liver-related mortality [31*].…”
Section: Addressing Hepatitis C Virus- Related Mortalitymentioning
confidence: 99%
“…Suárez-García I et al, reported patients who acquired HIV by sexual transmission compared with who acquired HIV infection through use of injected drugs has higher risk of late presentation, delayed antiretroviral therapy (ART) initiation, higher mortality and risk of progression to AIDS [33]. Therefore, in examining the risk factors for AIDS, it is also important to pay attention to the mediator factors; which can reduce or increase DALYs and mortality rate attributed to AIDS.…”
Section: Discussionmentioning
confidence: 99%
“…The tension between public health and criminal justice system approaches to HIV prevention is arguably most acutely felt by marginalized and otherwise criminalized groups, including PLWH who use illicit drugs. Studies consistently show that exposure to the criminal justice system is one of the most important barriers to engagement with HIV treatment and care (Cescon et al, 2011; Small, Kerr, Charette, Schechter, & Spittal, 2006, Suárez-García et al, 2016; Werb et al, 2008). People who use illicit drugs confront intersecting axes of disadvantage and stigma, experience high levels of surveillance from the criminal justice system, and face considerable social and structural barriers to retention in HIV treatment and care (Cescon et al, 2011; Kuchinad et al, 2016; Small et al, 2006; Suárez-García et al, 2016; Werb et al, 2008).…”
Section: Introductionmentioning
confidence: 99%